2019
DOI: 10.1101/517011
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Unrestrained ESCRT-III drives chromosome fragmentation and micronuclear catastrophe

Abstract: The ESCRT-III membrane fission machinery 1,2 restores nuclear envelope integrity during mitotic exit 3,4 and interphase 5,6 . Whereas primary nuclei resealing takes minutes, micronuclear envelope ruptures appear irreversible and result in catastrophic collapse associated with chromosome fragmentation and rearrangements (chromothripsis), thought to be a major driving force in cancer development 7-10 . Despite its importance 11-13 , the mechanistic underpinnings of nuclear envelope sealing in primary nuclei and … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

3
25
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 57 publications
3
25
0
Order By: Relevance
“…In our model, membrane recruitment could accelerate GFP-BAF removal by either passively increasing kinase concentration by nucleus resealing or actively targeting regulatory proteins to BAF-associated chromatin, similar to the correlation between membrane spreading and BAF release from chromatin during mitotic exit (Samwer et al, 2017). An alternative or additional hypothesis is that BAF remodeling at rupture sites reflects the membrane remodeling activity of the ESCRT-III complex, which drives LEMD2 spreading over the chromatin after micronucleus rupture (Vietri et al, 2019), similar to what we observe for BAF ( Figure 1F). We observed that large BAF foci are frequently unable to disassemble completely after nuclear integrity is restored, and consistent with previous observations of lamin A (Denais et al, 2016), we find these ruptureinduced BAF "scars" are refractory to re-rupture.…”
Section: Resultssupporting
confidence: 52%
See 1 more Smart Citation
“…In our model, membrane recruitment could accelerate GFP-BAF removal by either passively increasing kinase concentration by nucleus resealing or actively targeting regulatory proteins to BAF-associated chromatin, similar to the correlation between membrane spreading and BAF release from chromatin during mitotic exit (Samwer et al, 2017). An alternative or additional hypothesis is that BAF remodeling at rupture sites reflects the membrane remodeling activity of the ESCRT-III complex, which drives LEMD2 spreading over the chromatin after micronucleus rupture (Vietri et al, 2019), similar to what we observe for BAF ( Figure 1F). We observed that large BAF foci are frequently unable to disassemble completely after nuclear integrity is restored, and consistent with previous observations of lamin A (Denais et al, 2016), we find these ruptureinduced BAF "scars" are refractory to re-rupture.…”
Section: Resultssupporting
confidence: 52%
“…One possibility is that over-recruitment of LEMD2, or other NETs, could inhibit nuclear recompartmentalization through overactivation of ESCRT-III or excessive membrane recruitment. These conditions are both correlated with either the loss of nuclear membrane integrity or the prevention of membrane sealing after cell division or rupture (Appen et al, 2019;Penfield et al, 2019;Thaller et al, 2019;Vietri et al, 2019). Thus, the release of BAF from exposed chromatin during nuclear membrane rupture may be as critical as its recruitment to maintaining nucleus integrity.…”
Section: Resultsmentioning
confidence: 99%
“…We reasoned that spatiotemporal regulation of the LEM2/CHMP7 interaction would be essential both during mitotic exit and in the subsequent interphase. CHMP7 contains predicted Nuclear Export Sequences (NESs) in Helices 5 and 6 that are thought to limit its exposure to INM proteins, including LEM2, during interphase [10,18]. We confirmed the presence of active NESs in helices 5 and 6 of CHMP7 ( Figure S2A-S2E) and demonstrated that transient perturbation of exportin function resulted in nuclear accumulation of GFP-CHMP7 ( Figure S2D).…”
supporting
confidence: 53%
“…However, by transient transduction of cells with retroviruses driving weak GFP-CHMP7 2xNESexpression, we could demonstrate the inappropriate capture of LEM2 during interphase in GFP-CHMP7 2xNES--positive nuclear envelope and cytoplasmic clusters ( Figure S2H). These data highlight the essential nature of the trans-nuclear envelope segregation of LEM2 and CHMP7, suggesting the existence of a surveillance system poised to monitor the integrity of this barrier [10,18]. The second NES in Helix6 overlaps with a predicted type-1 MIM ( [19], Figure S2A), suggesting that this region may regulate both nucleocytoplasmic compartmentalisation and the ability of CHMP7 to engage the AAA-ATPase, VPS4.…”
mentioning
confidence: 87%
“…2 are generally resolved before the connected daughter cells enter the next S phase. Bridge resolution is accelerated by the exonucleolytic activity of TREX1, which accumulates on the DNA bridge after nuclear envelope rupture 4,[7][8][9] and results in formation of RPA-coated single-stranded (ss) DNA. Rearranged clonal cell lines isolated after progression through this in vitro telomere crisis showed frequent chromothripsis in a pattern similar to cancer: the chromothripsis events were limited to (parts of) chromosome arms rather than whole chromosomes 4,10 .…”
mentioning
confidence: 99%